From Jacobean “Biggest Miracle” to "Auto da Compadecida" by Ariano Suassuna: aspects of transculturation ocurred - Tavares Maleval, Maria do Amparo (Madrygal. Revista de Estudios Gallegos, 2017)
Among the Jacobean miracles collected in the Codex Calixtinus, which goes back to Galicia from the twelfth century, there is one that was considered “Biggest Miracle”. Narrates the resurrection of faithful (loyal) of the Apostle James the Greater through the intercession of this next to Santa Maria, obradora's done. In Brazil, the famous writer Ariano Suassuna (1927-2014), in Auto da Compadecida, took up the theme, bringing into play the resurrection of the character João Grilo. Maria presents itself, then, as a lawyer that character, defendant, next her Son, the accusations made against him by the devil. In the Auto epigraphs, Suassuna refers to sources in which it had founded its composition. It indicates that these are "novels of string", typical of the Northeast of Brazil, in which it notes the perpetuation of medieval tracks. The Celeste Court theme would have been for him known through the popular anonymous self O castigo da soberba. Our goal is to observe transcultural process of this miracle, certainly brought to Brazil by Iberian settlers, imbued with medieval mentality. We will seek to highlight the selected text, from the comparativist method, the ways in which they express and the values they defend or the sins that condemn, geo-historically considered.
Keywords: Codex Calixtinus; Booket Cordel; Brasilien Theater; Ariano Suassuna.